Electron-impact ionization of Fe3+. Issue 15 (January 2020) - Kynienė, A; Kučas, S; Masys, Š; Pakalka, S; Jonauskas, V
Synopsis: Electron-impact ionization cross sections are studied for levels of the ground and first excited con-figurations of the Fe 3+ ion. Convergence for the excitation-autoionization cross sections due to excitations to the high- nl shells is investigated. Single configuration and configuration interaction methods are used in the study. Scaling is applied to the distorted wave cross sections of the excitation-autoionization and collisional ionization processes.